2012
DOI: 10.1007/s00209-012-1073-1
|View full text |Cite
|
Sign up to set email alerts
|

Quandle homotopy invariants of knotted surfaces

Abstract: Given a finite quandle, we introduce a quandle homotopy invariant of knotted surfaces in the 4-sphere, modifying that of classical links. This invariant is valued in the third homotopy group of the quandle space, and is universal among the (generalized) quandle cocycle invariants. We compute the second and third homotopy groups, with respect to "regular Alexander quandles". As a corollary, any quandle cocycle invariant using the dihedral quandle of prime order is a scalar multiple of Mochizuki 3-cocycle invari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…The rack homotopy invariant of framed oriented links, obtained from the classifying spaces of racks, was introduced previously [9]. It was transformed into the quandle homotopy invariant [20,21] and the shadow homotopy invariant [29] of oriented links using the classifying spaces of quandles, which are constructed by adding extra cells to the classifying spaces of racks. In a similar manner, we construct a homotopy invariant of oriented links using the classifying spaces of biquandles.…”
Section: Biquandle Spaces and Their Homotopy Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…The rack homotopy invariant of framed oriented links, obtained from the classifying spaces of racks, was introduced previously [9]. It was transformed into the quandle homotopy invariant [20,21] and the shadow homotopy invariant [29] of oriented links using the classifying spaces of quandles, which are constructed by adding extra cells to the classifying spaces of racks. In a similar manner, we construct a homotopy invariant of oriented links using the classifying spaces of biquandles.…”
Section: Biquandle Spaces and Their Homotopy Groupsmentioning
confidence: 99%
“…(cf. [20,29,21]). By using Proposition 3.1 and Proposition 3.2, one can construct homological and homotopical link invariants in a similar manner to [4,20,21].…”
Section: Biquandle Spaces and Their Homotopy Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…We remark that when p is prime, dim ‫ކ‬ p H n Q (R p ; ‫ކ‬ p ) was calculated for any n by Nosaka [2009], who gave a system of generators of H n Q (R p ; ‫ކ‬ p ). When p is an odd integer, Nosaka [2010] showed that…”
Section: Cocycles Of Dihedral Quandlesmentioning
confidence: 99%